Existence and Stability Results for Boundary Value Problem for Differential Equation with ψ-Hilfer Fractional Derivative - Harikrishnan, S.; Kanagarajan, K.; Vivek, D. (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we discuss the existence, uniqueness and stability of boundary value problem for differential equations with ψ-Hilfer fractional derivative. The arguments are based upon Schaefer’s fixed point theorem, Banach contraction principle and ulam type stability.